An Analysis of Student’s at SMKN 4 Padang Difficulties in Reading Comprehension - Ramadhana Kusnawan, Luthfi Izazi; Hilmi, Lafziatul (Journal of English Language Teaching, 2024)
This research intended to know students’ problems at SMKN 4 Padang their reading comprehension. This program is implemented especially for grade twelve, that carried out for two days in first semester. This research includes a review of theories linked to the research concerns as well as the conceptual framework of the study. also, the researcher had done do practical field on this school before. so the researcher believed it was important to to analyze how the students’ perception on reading and teacher's methods. This study employed a quantitative methodology. The data were collected through questionnaire and interview. The questionnaire consisted 30 statements given to 53 students and interview consisted 13 questions given to 4 students. As a result of the study, most of the students not only gave the positive responses. but, also honest review about this problems in developing their reading skill. Providing the best advice for the new generation and how teachers teach students for the future. Most of They also hope in next future the teacher use the media for teaching like projector or something media, because of this learning activities which are more attractive and interesting. also, the student still think English lesson especially reading is difficult.